Preparing Students for the Public Health Workforce: The Role of Effective High-Impact Educational Practices in Undergraduate Public Health Program Curricula - Armstrong-Mensah, Elizabeth A.; Ramsey-White, Kim; Alema-Mensah, Ernest; Yankey, Barbara A. (Frontiers in Public Health, 2022)
There are several institutions of higher learning in the United States that award degrees in public health to undergraduate students. While these institutions serve as potential pipelines for the public health workforce, it is unclear if the curricula and training students receive from these institutions, really prepare them for the public health workforce or higher education. The questions sometimes asked are whether the programs offered by these institutions exist to provide students with a good understanding of public health issues so they can become good citizens for building a responsible society, or if it is to prepare students for graduate school. Regardless of what the goals are, students in undergraduate public health programs need to be exposed to curricula that adequately prepare them to enter well-defined careers in public health. Thus, institutions of higher learning offering degrees in public health to undergraduate students need to understand the market, assess, and understand the needs of public health agencies, and tailor course curricula to match those needs. Georgia State University established its undergraduate public health program in 2016. Since then, over 200 students have graduated from the program. The purpose of the study was to assess student perception of the role of high impact educational practices such as study abroad, signature experience, and undergraduate research curricula in preparing them for careers in public health.